RECONSTRUCTING THE LAW OF JILBAB IN THE QUR’AN: A COMPARATIVE STUDY OF CLASSICAL AND CONTEMPORARY INTERPRETATIONS - Ihram Ahmed Siregar; M. Aulia Urrahman; Rizki Amar; Andrie Nindy Dwiantari; Lisa Hertiana (istinbath, 2026)
This article examines and reconstructs the legal understanding of the jilbab through a comparative approach between the interpretations of classical and contemporary Islamic scholars. Debates on the jilbab are not limited to the normative aspects of religious texts, but also reflect the dynamic relationship between religion, culture, and social change. This study employs a qualitative method with a normative–comparative approach by analyzing Qur'anic verses related to the hijab, particularly Q. al-Nūr [24]: 31 and Q. al-Aḥzāb [33]: 59, as well as the interpretations of classical exegetes such as al-Ṭabarī, Ibn Kathīr, al-Qurṭubī, and al-Suyūṭī. These interpretations are then compared with the views of contemporary Muslim thinkers, including Saʿīd al-ʿAshmāwī, Muhammad Syahrūr, Amina Wadud, Yusuf al-Qaraḍāwī, and M. Quraish Shihab. The findings indicate a paradigmatic shift in interpretation from a textual–normative approach that emphasizes the formal obligation of the hijab toward a contextual and teleological approach oriented to the objectives of Islamic law (maqāṣid al-sharīʿah), such as the protection of dignity, modesty, and social justice. The reconstruction of hijab law proposed in this article underscores the importance of distinguishing between universal normative Islamic values and the practical forms of the jilbab, which are historical and contextual in nature. This distinction has particular relevance in a Muslim-majority country such as Indonesia, where debates over religious dress intersect with questions of religious diversity and legal formalization. This study is expected to contribute to the development of contemporary Islamic legal discourse that is more adaptive, humanistic, and responsive to social realities.